BILE LITHOGENICITY IN PATIENTS WITH TYPE 2 DIABETES AND ITS CORRECTION - O. A. Pavlenko; Ye. N. Babich (Бюллетень сибирской медицины)
We conducted a study to assess the bile lithogenicity in patients with type 2 diabetes mellitus (DM). We have found increased levels of cholesterol both in the gallbladder and hepatic bile. The study showed a decrease of cholatocholesterol coefficient (HHC), increase of lithogenic index Thomas–Hofmann and Rubens in all patients with type 2 diabetes, particularly in the gallbladder bile, indicating the colloidal destabilization of bile and an increased tendency to stone formation. Especially pronounced lithogenicity bile in patients with type 2 diabetes was associated with age in patients over 40 years of age and concomitant  overweight  or  obese  (BMI > 27 kg/m2).  After  a  course  of  ursodeoxycholic  acid  (UDCA)  at a dose of 15 mg/kg of body weight per day for 2.5–3 months was reduced lithogenicity gallbladder bile in patients with type 2 diabetes mellitus when the duration of disease was up to 5 years in 1.3 times, more than 5 years – in 1.5 times, more than 10 years – 1.7 times according to the index Thomas–Hofmann and Rubens.